1994
DOI: 10.1007/bf02088343
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of children with chronic idiopathic constipation

Abstract: To determine the outcome of chronic idiopathic constipation, we followed 62 children with chronic idiopathic constipation (mean age: 5.2 +/- 2.8 years) for a period of five years. Each child received the same initial treatment over a 12-week period and was then followed every three months. After five years from diagnosis, chronic idiopathic constipation persisted in 52% of the children; 47% who remained symptomatic were > 10 years old at the time of the five-year evaluation. Of the 27 who were constipated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
1
9

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 13 publications
5
83
1
9
Order By: Relevance
“…É observado na literatura que o início da constipação intestinal é mais freqüente nesse grupo etário 1,5,[7][8][9][10][19][20][21][22] . A prática do desmame, com a introdução de mingaus concentrados e alimentos sólidos pobres em fibras e o baixo aporte hídrico, pode ser a responsável pelo surgimento do sintoma neste período.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…É observado na literatura que o início da constipação intestinal é mais freqüente nesse grupo etário 1,5,[7][8][9][10][19][20][21][22] . A prática do desmame, com a introdução de mingaus concentrados e alimentos sólidos pobres em fibras e o baixo aporte hídrico, pode ser a responsável pelo surgimento do sintoma neste período.…”
Section: Discussionunclassified
“…A constipação intestinal é um dos distúrbios intestinais mais freqüentes e persistentes da infância [1][2][3][4][5] . Embora seja causa freqüente de consultas em ambulatórios pediátricos gerais e de gastrenterologia, o sintoma é pouco identificado, especialmente em sua fase inicial, pois a morbidade discreta não desperta atenção e/ou preocupação suficientes para que haja a queixa espontânea nas consultas pediátricas de rotina [6][7][8][9][10][11] .…”
Section: Introductionunclassified
“…Despite these treatment regimens, long-term follow-up studies have demonstrated that ϳ50% of these children continue to require therapy for long periods of time. 2 In the past 2 decades, manometric evaluation of anorectal function showed paradoxic contraction of the anal sphincter during defecation in 35% to 63% of constipated children. [3][4][5] This phenomenon may be caused by attempts to avoid defecation because of fears and pains experienced during defecation of hard stools early in life.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these treatment regimens, long-term follow-up studies have demonstrated that ϳ50% of these children continue to require therapy for long periods of time. 2 From the …”
mentioning
confidence: 99%
“…Mothers of children seen for functional constipation at gastroenterology clinics often recall early onset of their child's symptoms (1,3,11,15,20,21,24,31,35) , and in Botucatu Medical School pediatric gastroenterology outpatient unit a long time gap was observed between the recalled onset of symptoms and first attendance, respectively at median 3 and 53 months of age (18) . But, data may be biased by the reliability of maternal recall after a long time lapse and by referral of the most severe cases.…”
Section: Introductionmentioning
confidence: 99%